The factors that contribute to the significant growth toward Medical and Health Insurance (MHI) product / Shazwani Muda - Muda, Shazwani (2011)
Recently, Medical and Health Insurance (MHI) business is emerging as an important sector of the insurance industry, complementing the public healthcare system by providing healthcare protection to certain segments of society. MHI business has been identified as a sector with strong potential to develop into an important component of the insurance industry, the orderly development of the sector for a sustainable growth as well as the protection of consumer interests become paramount as consumers increasingly turn to the insurance industry for protection to meet their healthcare financing needs. These research objectives are to determine the factors that contribute to the significant growth in Medical and Health Insurance (MHI) Product and to identify the major factors that contribute to the significant growth toward Medical and Health Insurance (MHI) product. Chapter one consist of the introduction and background of the study. Chapter two consist literature review, chapter three is about the research methodology, chapter four is about data analysis and interpretation of data and lastly for chapter five included conclusion and recommendation.